The COVID-19 Pandemic's impact on sustainability and expansion of a Pediatric Early Warning System in resource-limited hospitals - Wiphatphumiprates, PP (2023)
Background: The COVID-19 pandemic impacted healthcare delivery worldwide, including pediatric cancer care, with a disproportionate effect in resource-limited settings. This study evaluates its impact on existing quality improvement (QI) programs. Methods: We conducted 71 semi-structured interviews of key stakeholders at five resource-limited pediatric oncology centers participating in a collaborative to implement Pediatric Early Warning System (PEWS). Interviews were conducted virtually using a structured interview guide, recorded, transcribed, and translated into English. Two coders developed a codebook of a priori and inductive codes and independently coded all transcripts, achieving a kappa of 0.8–0.9. Thematic analysis explored the impact of the pandemic on PEWS. Results: All hospitals reported limitations in material resources, reduction in staffing, and impacts on patient care due to the pandemic. However, the impact on PEWS varied across centers. Identified factors that promoted or limited ongoing PEWS use included the availability of material resources needed for PEWS, staff turnover, PEWS training for staff, and the willingness of staff and hospital leaders to prioritize PEWS. Consequently, some hospitals were able to sustain PEWS; others halted or reduced PEWS use to prioritize other work. Similarly, the pandemic delayed plans at all hospitals to expand PEWS to other units. Several participants were hopeful for future expansion of PEWS post-pandemic. Conclusion: The COVID-19 pandemic created challenges for sustainability and scale of PEWS, an ongoing QI program, in these resource-limited pediatric oncology centers. Several factors mitigated these challenges and promoted ongoing PEWS use. These results can guide strategies to sustain effective QI interventions during future health crises.